Intrinsic Broadband White‐Light Emission from Ultrastable, Cationic Lead Halide Layered Materials. Issue 46 (17th October 2017) - Zhuang, Zewen; Peng, Chengdong; Zhang, Guiyang; Yang, Huimin; Yin, Jinlin; Fei, Honghan
Abstract: We report a family of cationic lead halide layered materials, formulated as [Pb2 X2 ] 2+ [ − O2 C(CH)2 CO2 − ] (X=F, Cl, Br), exhibiting pronounced broadband white‐light emission in bulk form. These well‐defined PbX‐based structures achieve an external quantum efficiency as high as 11.8 %, which is comparable to the highest reported value (ca.9 %) for broadband phosphors based on layered organolead halide perovskites. More importantly, our cationic materials are ultrastable lead halide materials, which overcome the air/moisture‐sensitivity problems of lead perovskites. In contrast to the perovskites and other bulk emitters, the white‐light emission intensity of our materials remains undiminished after continuous UV irradiation for 30 days under atmospheric conditions (ca.60 % relative humidity). Our mechanistic studies confirm that the broadband emission is ascribed to short‐range electron‐phonon coupling in the strongly deformable lattice and generated self‐trapped carriers. Abstract : White out : Cationic lead halide layered materials formulated as [Pb2 X2 ] 2+ [ − O2 C(CH)2 CO2 − ] (X=F, Cl, Br) are ultrastable, broadband white‐light emitters with an external quantum efficiency as high as 11.8 % and long‐term photostability under atmospheric conditions, which overcome the air/moisture‐sensitivity problems of lead perovskites.